What Jesus Demands From The World - "Piper, John" ("Wheaton, Illinois :")
"Includes index. Introduction: the aim of the book -- A word to biblical scholars -- Demand #1: you must be born again -- Demand #2: repent -- Demand #3: come to me -- Demand #4: believe in me -- Demand #5: love me -- Demand #6: listen to me -- Demand #7: abide in me -- Demand #8: take up your cross and follow me -- Demand #9: love God with all your heart, soul, mind, and strength -- Demand #10: rejoice and leap for joy -- Demand #11: fear Him who can destroy both soul and body in hell -- Demand #12: worship God in spirit and truth -- Demand #13: always pray and do not lose heart -- Demand #14: do not be anxious about the necessities of daily life -- Demand #15: do not be anxious about the threats of man -- Demand #16: humble yourself -- By making war on pride -- Demand #17: humble yourself -- In childlikeness, servanthood, and broken-hearted boldness -- Demand #18: do not be angry -- Trust God' providence -- Demand #19: do not be angry -- Embrace mercy and forgiveness -- Demand #20: do the will of my Father who is in heaven -- Be justified by trusting jesus -- Demand #21: do the will of my Father who is in heaven -- Be transformed by trusting Jesus -- Demand #22: strive to enter through the narrow door -- For all of life is war -- Demand #23: strive to enter through the narrow door -- For jesus fulfills the new covenant -- Demand #24: strive to enter through the narrow door -- For you are already in the kingdoms power -- Demand #25: your righteousness must exceed that of the Scribes and Pharisees -- For it was hypocritical and ugly -- Demand #26: your righteousness must exceed that of the Scribes and Pharisees -- Clean the inside of the cup -- Demand #27: your righteousness must exceed that of the Scribes and Pharisees -- For every healthy tree bears good fruit -- Demand #28: love your enemies -- Lead them to the truth -- Demand #29: love your enemies -- Pray for those who abuse you -- Demand #30: love your enemies -- Do good to those who hate you, give to the one who asks -- Demand #31: love your enemies -- To show that you are children of God -- Demand #32: love your neighbor as yourself -- For this is the law and the prophets -- Demand #33: love your neighbor with the same commitment -- You have to your own well-being -- Demand #34: love your neighbor as yourself and as Jesus loved us -- Demand #35: lay up for yourselves treasures in heaven -- By giving sacrificially and generously -- Demand #36: lay up for yourselves treasures in heaven -- And increase your joy in Jesus -- Demand #37: lay up for yourselves treasures in heaven -- It is your fathers good pleasure to give you the kingdom -- Demand #38: do not take an oath -- Cherish the truth and speak it simply -- Demand #39: do not take an oath -- Let what you say be simply yes or no -- Demand #40: what God has joined together let no man separate -- For marriage mirrors God's covenant with us -- Demand #41: what God has joined together let no man separate -- For whoever divorces and marries another commits adultery -- Demand #42: what God has joined together let no man separate -- Man, one woman, by grace, till death -- Demand #43: render to Caesar the things that are Caesars' -- And to God the things that are God's -- Demand #44: render to Caesar the things that are Caesars' -- As an act of rendering to god what is gods -- Demand #45: do this in remembrance of me -- For i will build my church -- Demand #46: do this in remembrance of me -- Baptize disciples and eat the Lord's supper -- Demand #47: let your light shine before others -- That they might give glory to your Father who is in heaven -- Demand #48: let your light shine before others -- The joyful sacrifice of love in suffering -- Demand #49: make disciples of all nations -- For all authority belongs to Jesus -- Demand #50: make disciples of all nations -- For the mission cannot fail."
Keywords: "JESUS CHRIST -- TEACHINGS.;BIBLE. N.T. GOSPELS -- CRITICISM, INTERPRETATION,"